(3fNHI GddHjH GdYGde aj GdcTa Yf CSQGQ GdYhGdes
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai CeG HYO aEfg deG SHb Gdbhd Ydi eG bOefG GdcdGe Ydjg ef hVY GdbhGfjf GdeHShWI s
(3BNQgG (B:s
(3hGdLeY hGdVQH hGdWQM hVYJ dPdc CUdkG hGddg GdeYjf hGddg MSHi hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs